A G‐quadruplex/hemin DNAzyme‐based microchip electrophoresis chemiluminescence assay for highly sensitive detection of biotin in flour. Issue 16 (2nd May 2019) - Li, Jian; Li, Shuting; Zhao, Jingjin; Huang, Yong; Zhao, Shulin
Abstract: Quantitative analysis of biotin in biological fluids, foods, and pharmaceutical is important for diagnosis and treatment of biotin‐related diseases and health maintenance. In this work, a novel G‐quadruplex/hemin DNAzyme‐based microchip electrophoresis chemiluminescence (CL) assay method was established for rapid and highly sensitive detection of biotin. This method is based on the specific binding between biotin and streptavidin, the catalytic CL characteristics of G‐quadruplex/hemin DNAzyme to the oxidation–reduction reaction of hydrogen peroxide with luminol, and the on‐line separation function of microchip electrophoresis. Under the optimal experimental conditions, on‐chip biotin analysis was achieved within 1 min. The CL intensity is linearly proportional to the concentration of biotin in the range of 13–630 nM with a detection limit of 6.4 nM. The proposed method has been applied for the detection of biotin in flour, biotin contents in three flour samples are found in the range of 199–223 ng/g with a mean value of 214 ng/g. The recoveries were in the range of 94–103%. With excellent sensitivity and good selectivity, the proposed method could be applied in a wide range of biological fluids, foods, and pharmaceutical analysis.